Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan Informasi Akuntansi Pelaku UMKM - Alifiah Wulansari Mustofa; Sri Trisnaningsih (Jurnal Akuntansi Profesi, 2021)
One of the problems that occur in MSMEs can be overcome by the use of accounting information, which can be used as basic capital in making decisions related to business development. This study aims to identify and analyze accounting knowledge, business experience, accounting training and business scale on the use of accounting information. The research uses quantitative methods. The population used in this study were 163 units of MSMEs coffee shops in Surabaya. The sample in this study was taken using the Slovin formula, while the sampling technique used nonprobability sampling with purposive sampling in order to obtain a sample of 62 units. Data obtained directly by questionnaires to respondents. The analysis technique in this study uses multiple linear regression analysis with IBM SPSS Statistics 22 software. The results of this study indicate that (1) accounting knowledge has a positive effect on the use of accounting information; (2) business experience has no positive effect on the use of accounting information; (3) accounting training has a positive effect on the use of accounting information; (4) business scale has a positive effect on the use of accounting information.